PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAMES TOURNAMENT) DENGAN MEDIA KOKAMI DALAM MENINGKATKAN HASIL BELAJAR BIOLOGI - Saputra, Fendy; Hikamah, Siti Roudlotul; Rohman, Minahur (JURNAL BIOSHELL, 2013)
This study aims to determine learning out comes and student activity in SMPN 5 Tanggul class VIII D with implementing cooperative learning type TGT (Team Games Tournament). This type of research that is in use is a classroom action research. The procedure used is a model cycles, each cycle consisting of four phase : planning, action, observation and research reflection. Type TGT cooperative learning by using media as a learning kokami obtained some findings, namely in the first cycle classical completeness of 69.2%, while in the second cycle classical completeness obtained 94.9%. Increased activity of learning (tests) students, the results of the analysis of student active the first cycle obtained average value of 77%, where as the values obtained in the second cycle an average of 87%. From these results, it can be described in general that by implementing cooperative learning type TGT (Team Games Tournament) using kokami as learning media can improve learning out comes and student activities.Keywords :  learning out comes, student activity, TGT (Team Games Tournament), kokami